2017
DOI: 10.1038/s41540-017-0025-0
|View full text |Cite|
|
Sign up to set email alerts
|

Computer modeling defines the system driving a constant current crucial for homeostasis in the mammalian cochlea by integrating unique ion transports

Abstract: The cochlear lateral wall—an epithelial-like tissue comprising inner and outer layers—maintains +80 mV in endolymph. This endocochlear potential supports hearing and represents the sum of all membrane potentials across apical and basolateral surfaces of both layers. The apical surfaces are governed by K+ equilibrium potentials. Underlying extracellular and intracellular [K+] is likely controlled by the “circulation current,” which crosses the two layers and unidirectionally flows throughout the cochlea. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…HEK293T cells expressing recSLC12A2 proteins carrying each of the three variants showed significantly decreased Cl − influx activity. Moreover, we observed abundant SLC12A2 signals in the basolateral membrane of strial marginal cells and lateral wall fibrocytes in non-human primate cochlea, a distribution identical to that reported for rodent cochleae [16], suggesting a conserved role for SLC12A2 in homeostasis of the endolymph by recycling K + from the perilymph to the stria vascularis in mammalian cochlea, including in humans [3,4]. The congenital, severe-to-profound hearing loss in our patients is consistent with the phenotype of Slc12a2-deficient M. musculus [16][17][18][19].…”
Section: Association Of Slc12a2 With Hearing Loss In Humanssupporting
confidence: 82%
See 2 more Smart Citations
“…HEK293T cells expressing recSLC12A2 proteins carrying each of the three variants showed significantly decreased Cl − influx activity. Moreover, we observed abundant SLC12A2 signals in the basolateral membrane of strial marginal cells and lateral wall fibrocytes in non-human primate cochlea, a distribution identical to that reported for rodent cochleae [16], suggesting a conserved role for SLC12A2 in homeostasis of the endolymph by recycling K + from the perilymph to the stria vascularis in mammalian cochlea, including in humans [3,4]. The congenital, severe-to-profound hearing loss in our patients is consistent with the phenotype of Slc12a2-deficient M. musculus [16][17][18][19].…”
Section: Association Of Slc12a2 With Hearing Loss In Humanssupporting
confidence: 82%
“…SLC12A2 is the entry site for Na + , K + , and 2Cl − from the intrastrial space to the strial marginal cells in the cochlear lateral wall [4]. Slc12a2-deficient M. musculus show loss of scala media [16][17][18][19], while homozygous Slc12a2 deficiency results in loss of endolymph volume, collapse of the otic vesicles with functional sensory hair cells, and a vestibular disorder phenotype in Danio rerio larvae [41].…”
Section: Association Of Slc12a2 With Hearing Loss In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite continuing interest in SV cell types, an understanding of cellular heterogeneity, including a comprehensive understanding of SV cell type-specific transcriptional profiles, is incomplete. While several in vivo, in vitro, and in silico studies have identified key roles for particular strial cell types in EP generation, including MCs, ICs, and BCs (Takeuchi et al, 2000;Nin et al, 2008;Mori et al, 2009;Hibino et al, 2010;Chen and Zhao, 2014;Yoshida et al, 2015;Nin et al, 2017), the mechanisms by which the various cell types work together to accomplish EP generation as well as other strial functions remains largely undefined (Ohlemiller, 2009). Furthermore, the gene regulatory networks that provide the basis for these EP-generating mechanisms remain largely undefined.…”
Section: Introductionmentioning
confidence: 99%
“…For in silico analysis (Fig. 2), the fibrocyte-integrated Nin-Hibino-Kurachi (fi-NHK) model developed in our earlier study was used (Nin et al 2017). Accordingly, the principles of the model described in this section are excerpted from the previous articles with the original authors' permission.…”
Section: Computational Simulationmentioning
confidence: 99%